PENGARUH PEMBELAJARAN MICRO TEACHING DAN PROGRAM PENGALAMAN LAPANGAN (PPL) TERHADAP MINAT MENJADI GURU PADA MAHASISWA - -, Novita Sari -; -, Trisno Martono -; -, Sri Wahyuni - (Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
ABSTRACT            This research is aimed to identify (1) the influence of Micro Teaching learning and Field Experience Program (PPL) towards the interest of becoming a teacher of the Economic Education students in the year of 2017; (2) the influence of Micro Teaching learning towards  the interest of becoming a teacher of the Economic Education students in the year of 2017; (3) the influence of Field Experience Program (PPL) towards the interest of becoming a teacher of the Economic Education students in the year of 2017.             This research includes as a qualitative research. The research includes as a population research. The data was collected by distributing questionnaires. The validity of the data was obtained through the result of tryout of 30 respondents. The data were analyzed by using multiple linear regression analysis.              The research finding shows that: (1) the value of F-test is obtained Fcount>Ftable (5,736>3,14) with the value of p = 0,005, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence between Micro Teaching learning and Field Experience Program (PPL) simultaneosly towards the interest of becoming a teacher. (2) the value of t-test with the variable of Micro Teaching learning is tcount>ttable (2,009>1,99) with the value of p = 0,049, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence between Micro Teaching learning and Field Experience Program (PPL) partially towards the interest of becoming a teacher. (3) the value of t-test with the variable of Field Experience Program (PPL) is tcount>ttable (2,157>1,99) with the value of p = 0,035, therefore Ho is rejected and Ha is accepted. It means that there is a significant influence of the variable of Field Experience Program (PPL) partially towards the interest of becoming a teacher. (4) the determinant coeffisient (Adjusted R Square) is 0,127. It can be concluded that 12,7% of interest of becoming a teacher is influenced by Micro Teaching learning and Field Experience Program (PPL), meanwhile the rest of  87,3% is influenced by various factors which are not included in this research. ABSTRAK            Penelitian ini memiliki tujuan agar mengatahui (1) pengaruh pembelajaran micro teaching dan PPL terhadap minat menjadi guru mahasiswa pendidikan ekonomi tahun 2017; (2) pengaruh pembelajaran micro teaching terhadap minat menjadi guru mahasiswa pendidikan ekonomi tahun 2017; (3) PPL terhadap minat menjadi guru mahasiswa pendidikan ekonomi tahun 2017.            Penelitian ini adalahpenelitian kuantitatif dan termasuk penelitian populasi. Sumber data berupa data hasil menyebar angket. Teknik dalam mengumpulkan data yaitu kuesioner. Validitas data diperoleh melalui hasil uji cobadari 30 responden. Teknik analisis data menggunakan analisis regresi linier berganda.            Hasil penelitian menunjukkan : (1) nilai uji F menunjukkan Fhitung>Ftabel  (5,736>3,14) dengan nilai p=0,005, sehingga Ha diterima dan Ho ditolak. Hal ini berarti terdapat pengaruh yang signifikan antara variabel pembelajaran micro teaching dan PPL secara simultan terhadap minat menjadi guru (2) nilai uji t variabel pembelajaran micro teaching adalah thitung>ttabel (2,009>1,99) dengan nilai p=0,049 sehingga Ha diterima dan Ho ditolak. Hal ini berarti terdapat pengaruh yang signifikan variabel pembelajaran micro teaching secara parsial terhadap minat menjadi guru (3) nilai uji t variabel PPL adalah thitung>ttabel (2,157>1,99) dengan nilai p=0,035 sehingga Ha diterima dan Ho ditolak. Hal ini berarti terdapat pengaruh yang signifikan variabel PPL secara parsial terdapat minat menjadi guru (4) koefisien determinasi sebesar 0,127. Hal ini dapat diartikan bahwa 12,7% minat menjadi guru dipengaruhi oleh pebelajaran micro teaching dan PPL, sedangkan 87,3% sisanya dipengaruhi oleh berbagai faktor selain yang diteliti dalam penelitian ini.